The Effectiveness of Implementing the Interactive Multimedia Based Quantum Learning Model on the Short Story Writing Skills - Rizky Mutiara Sani; Bambang Yulianto (Raja Zulkarnain Education Foundation, 2026)
The problems in learning in class IX of SMPN 40 Surabaya, which is still teacher-centered and dependent on textbooks, prompted this study. This condition makes students passive, easily bored, and unable to write short stories optimally. Interviews with Indonesian language teachers reinforced these findings, confirming that the Quantum Learning model and interactive multimedia had never been implemented. This situation highlights the need for attractive, interactive, and experience-oriented learning innovations. The purpose of this study was to describe the short story writing skills of ninth-grade students at SMPN 40 Surabaya before and after the implementation of the interactive multimedia-based Quantum Learning model and the improvements achieved. The method used was quantitative with a one-group pre-test post-test pre-experimental design. The research population was all ninth-grade students at SMPN 40 Surabaya in the 2025/2026 academic year, while the sample was class IX-I consisting of 27 students selected through cluster random sampling. The data collection technique used a pre-test and post-test. Meanwhile, the analysis technique used descriptive statistics, Shapiro-Wilk normality test, hypothesis testing in the form of paired t-tests, and N-Gain. The results of the study showed an increase in students’ short story writing skills from a pre-test average score of 68.33 to 82.59 on the post-test. The normality test showed that the data was normally distributed, while the t-test produced a Sig. (2-tailed) score of 0.000 < 0.05 and a t-count > t-table, indicating a significant difference between the two values. The N-Gain value of 0.4425 falls into the moderate category, indicating that the interactive multimedia-based Quantum Learning model is effective in improving the short story writing skills of ninth-grade students at SMPN 40 Surabaya.